Effective stability in a moist baroclinic wave. (15th August 2014) - Booth, James F.; Polvani, Lorenzo; O'Gorman, Paul A.; Wang, Shuguang
Abstract It has been proposed that the impact of moisture on atmospheric eddy circulations can be approximated using a reduced effective stratification defined in terms of a parameter λ, which quantifies the asymmetry between upward and downward motions. Here λ is analyzed for the midlatitude regime using baroclinic lifecycles computed with the Weather Research and Forecast model. Vertical velocities are compared for integrations with different moisture conditions, and the change in λ is quantified and interpreted. λ is shown to be largely insensitive to grid resolution, and the effective stratification captures the impact of moisture provided initial relative humidity is sufficiently high.